VDR Signaling via the Enzyme NAT2 Inhibits Colorectal Cancer Progression - Zhu, Chaojun; Wang, Zihuan; Cai, Jianqun; Pan, Chunqiu; Lin, Simin; Zhang, Yue; Chen, Yuting; Leng, Mengxin; He, Chengcheng; Zhou, Peirong; Wu, Changjie; Fang, Yuxin; et al. (Frontiers in Pharmacology, 2021)
Recent epidemiological and preclinical evidences indicate that vitamin D inhibits colorectal cancer (CRC) progression, whereas the mechanism has not been completely elucidated. This study was designed to affirm the protective effects of vitamin D and identify crucial targets and regulatory mechanism in CRC. Firstly, we affirmed vitamin D suppressed aggressive phenotype of CRC in vitro and in vivo experiments. Based on a network pharmacology analysis, N-acetyltransferases 2 (NAT2) was identified as the potential key target of vitamin D against CRC. Bioinformatics analysis and molecular biology experiments indicated that NAT2 was down-regulated in CRC specimens and low expression of NAT2 significantly increased the risk of metastasis and shortened survival in CRC. Furthermore, we found that NAT2 suppressed proliferation and migration capacity of CRC cells, and JAK1/STAT3 signaling pathway might be the underlying mechanism. Moreover, western blot and immunofluorescence staining assays demonstrated vitamin D promoted NAT2 expression, and chromatin immunoprecipitation assay indicated vitamin D receptor (VDR) transcriptionally regulated NAT2. These findings expand the potential uses of vitamin D against CRC and introduce VDR-NAT2 signaling as a potential diagnostic and therapeutic target for CRC.